Efficient modeling of sharp-edge acoustofluidics - Pavlic, Alen; Roth, Lukas; Harshbarger, Cooper Lars; Dual, Jürg (Frontiers in Physics, 2023)
Sharp-edge structures exposed to acoustic fields are known to produce a strong nonlinear response, mainly in the form of acoustic streaming and acoustic radiation force. The two phenomena are useful for various processes at the microscale, such as fluid mixing, pumping, or trapping of microparticles and biological cells. Numerical simulations are essential in order to improve the performance of sharp-edge-based devices. However, simulation of sharp-edge structures in the scope of whole acoustofluidic devices is challenging due to the thin viscous boundary layer that needs to be resolved. Existing efficient modeling techniques that substitute the need for discretization of the thin viscous boundary layer through analytically-derived limiting velocity fail due to large curvatures of sharp edges. Here, we combine the fully viscous modeling approach that accurately resolves the viscous boundary layer near sharp edges with an existing efficient modeling method in the rest of a device. We validate our hybrid method on several 2D configurations, revealing its potential to significantly reduce the required degrees of freedom compared to using the fully viscous approach for the whole system, while retaining the relevant physics. Furthermore, we demonstrate the ability of the presented modeling approach to model high-frequency 3D acoustofluidic devices featuring sharp edges, which will hopefully facilitate a new generation of sharp-edge-based acoustofluidic devices.